IMPROVING EQUIVALENCY EDUCATION PROGRAM PACKAGE C STUDENTS’ ENGLISH VOCABULARIES USING FLASHCARD MEDIA - Pipih Supiah; Agus Hasbi Noor; Sri Nurhayati (Jurnal Empowerment, 2024)
The purpose of this study was to determine the extent to which English vocabulary learning via flashcard media is effective in Package C Equivalency Education Program Students English lesson. This research used a qualitative approach with descriptive method. The data collection began with interview and observation of tutors and CLC managers, in which respondents were asked to provide responses or opinions on the effectiveness of English vocabulary learning through flashcard media. Research participants also were given an initial test (pretest) to determine their vocabulary knowledge, with the lowest score of 20 and the highest score of 40, followed by action or reflection, and finally retested (posttest) with a maximum score of 40 and a minimum score of 60. The findings of this study indicate that using flashcards media could improve equivalency education program Package C students’ English vocabularies.